Manajemen Strategi Kepala Madrasah Dalam Mengimplementasikan Kurikulum Madrasah Diniyah (Studi Kasus di Pondok Pesantren Al-Mardliyah Tambakberas Jombang) - Fitriyana Pratama; Marno Marno; Ahmad Barizi (Jurnal Ilmiah Profesi Pendidikan, 2026)
Madrasa principals play a crucial role in ensuring the effective implementation of educational programs, particularly in diniyah madrasa settings. Effective strategic management is therefore essential to achieve curriculum goals. This study aims to analyze the strategic management of the madrasa principal in implementing the diniyah madrasa curriculum at Al-Mardliyah Islamic Boarding School, Tambakberas Jombang. This research employs a qualitative approach with a case study design. Data were collected through interviews, observations, and documentation, and analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. Data validity was ensured through source and method triangulation. The results show that curriculum implementation is conducted systematically through three main stages: planning, implementation, and evaluation. Planning is carried out participatively with curriculum innovations based on students’ ability levels. Implementation is conducted adaptively by integrating traditional pesantren methods with contextual learning approaches. Evaluation is conducted continuously through monitoring and reflection for ongoing improvement. The study concludes that the madrasa principal has a strategic role as a leader who directs and drives curriculum implementation, although challenges such as limited human resources, facilities, and funding remain.